English as an international language and Google's pronunciation tool (International Seven Journal of Multidisciplinary, 2024)
Introduction: Google's pronunciation tool is widely used by English teachers to improve their students' pronunciation. It is also, and above all, an accessible tool for online teaching, as it is available free of charge to all users of the platform. Aim: This article questions the extent to which this use can be beneficial or detrimental to the teaching of speaking skills. Materials and Methods: This tool was analyzed in this article in the light of the concept of English as a Lingua Franca (ILF), which proposes a decolonial approach to language teaching and learning, disconnecting the concept of proficiency from the perfect imitation of the pronunciation of native speakers from the countries with the greatest hegemonic power, mainly the United States and England. We explore the evolution of English teaching in Brazil, highlighting a post-structuralist approach to language, which questions the traditional view of language as a structured system ready to be “acquired”. In this sense, it advocates a flexible approach that values the different variants of English, including those spoken by non-native speakers. In this article, we investigate the use of the tool by a B1 (pre-intermediate) level student. Screen shots were recorded showing the tool's assessment of that student's pronunciation. Results: The Google tool, although useful, is criticized here for restricting itself to prestige variants and promoting a purist view of pronunciation. The corrections proposed by the tool demonstrate a restricted view of the language, suggesting modifications that would not interfere with the intelligibility of the student's speech. Conclusion: We propose an expansion of pronunciation options and a more flexible approach to assessing speech intelligibility, reflecting linguistic diversity. These considerations are urgent given the importance of Information and Communication Technologies (ICTs) in contemporary teaching.